Photonic Materials: On the Molecular Mechanism of a Photo‐Responsive Phase Change Memory (Adv. Theory Simul. 5/2021). Issue 5 (5th May 2021) - Amirjalayer, Saeed
Abstract : A population swapping genetic algorithm is introduced in article 2100017 by Saeed Amirjalayer to efficiently develop an atomistic potential describing the out‐of‐equilibrium dynamics of an azobenzene‐based phase change material. Based on this approach, a balanced representation of the energy landscape is ensured. Thus, the photo‐induced structural evolution during the phase transformation of the periodic matrix is captured at the atomic level, providing new insight into molecular‐based photonic materials.